Study of Apple Varieties in High-Density Plantation under Cold Dry Temperate Conditions of Kinnaur - Kumar, Arun; Singh, Gopal; Kumar, Vijay; Kumari, Meena; Dhiman, Sushil (International Journal of Bio-resource and Stress Management, 2022)
The study was carried out to evaluate four apple varieties on different rootstocks under high-density plantations in the cold temperate region of Kinnaur for growth, yield and quality attributes. The experiment evaluated four apple varieties ‘Red Cap Valtod/MM 106’, ‘Red Velox/M9’, ‘Jeromine/M9’ and ‘Super Chief/MM 106’ planted at a spacing of 2.5×1.0 m2 in Randomized Block Design, with four replicates. From the evaluation of data on growth, floriculture and quality standards, it was clear that var. Jeromine/M9 followed by Red Velox/M9 has recorded better horticultural performance than other varieties studied. Among different varieties Red Velox/M9 recorded maximum shoot extension growth (22.65 cm), trunk girth (47.27 mm) and tree height (340.02 cm), tree spread (175.52 E-W and 181.68 cm N-S), number of fruit set tree-1 (41.85), fruit Breadth (78.90 mm), fruit weight (207.39 g fruit-1), TSS (10.11 °Brix), whereas, maximum fruit set (25.48%), fruit length (71.74 mm), yield (3.59 kg tree-1) and productivity (14.35 MT Hac-1) was recorded in cultivar Jeromine/M9. However, the maximum number of fruits tree-1 was observed in the variety Red Cap Vatod/MM 106. Variety, Red Velox /M9 was found to be superior for growth, flowering, yield and quality characteristics with good market potential under Kinnaur conditions.